Development and Validation of HPTLC Method for Simultaneous Quantitation of Embelin and Assay of Marketed Formulation - Rahul.J, Sudani (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTEmbelia ribes burm f., also known as Vidanga, is one of the oldest herbs in Indian traditional medicine. Embelia ribes have a long history of use in ayurvedic system of medicine in various forms like churna, asava, aristha and taila. It is used mainly as an anthelmintic, carminative and stimulant. A selective, precise and accurate High Performance Thin Layer Chromatography (HPTLC) method has been developed for the simultaneous quantitation of Embelin in Vidanga churna formulations. The method employed TLC aluminium plate (10 cm x 10cm x 250 µm) precoated with silica gel 60 F254 as a stationary phase. The solvent system consists of Chloroform: Ethyl acetate: Formic acid (5:4:1 v/v/v). Densitometric analysis was carried out in the absorbance mode at 291 nm using Camag TLC scanner-III. Developed HPTLC method showed good regression (r2= 0.9986 ± 0.0020) and the recovery of Embelin was in the range of 99.09 – 102.01%. The limit of detection and limit of quantitation were found to be 61.28ng/spot and 185.71ng/spot respectively. The method was validated for precision, recovery, limit of detection and limit of quantitation. The proposed HPTLC method was found to be simple, precised and accurate and can be used for the quality control of the raw materials as well as formulations.